Efektivitas Ekstrak Daun Pepaya (Carica papaya L.) sebagai Inhibitor pada Baja Karbon AISI 1020 dalam Medium Korosif NaCl 3% - Repangga Yudi Aditama; Ediman Ginting Suka; Syafriadi Syafriadi (Jurnal Teori dan Aplikasi Fisika, 2019)
Papaya leaf extract used as an inhibitor in carbon steel sample AISI 1020, was immersed in a 3% carboxy NaCl medium. By varying the immersion time of 4 days and 8 days, and also the concentration of inhibitor 0%, 3%, 5% and 7%. After the treatment of the sample obtained the slowest corrosion rate calculation results in AISI 1020 4.5 samples and the fastest in the AISI 1020 8.7 sample. The inhibitor used has the most efficient efficiency value in the AISI 1020 4.5 sample and the inefficient value in the AISI 1020 4.7 sample. The XRD characterization results show that the crystalline structure formed is BBC with pure Fe phase. The SEM characterization shows the surface morphology of the steel sample, visible in the sample without the addition of more inhibitors than the sample with the added inhibitor. In addition, cracks do not appear on the AISI 1020 4.5 sample. Characterization of EDS in the sample seen elements of Oxygen (O) and Clorin (Cl) which indicates that the sample has been corroded.